CILIOCHOROIDAL EFFUSION AND ACUTE MACULAR NEURORETINOPATHY ASSOCIATED WITH CERVICAL TRACTION THERAPY. Issue Volume 12:Issues 1(2018) (2018) - Dedania, Vaidehi S.; Ghodasra, Devon H.; Kay, Christine N.; Roseman, Robert; Johnson, Mark W.
Abstract : Purpose: To report an unusual case of ciliochoroidal effusion and presumed acute macular neuroretinopathy associated with cervical traction therapy for the treatment of cervical spinal stenosis. Methods: Case report. Results: A 75-year-old man reported sudden onset of a wedge-shaped paracentral scotoma in the right eye. Fundus examination showed a ciliochoroidal effusion in the right eye. Optical coherence tomography revealed intraretinal fluid in both eyes without leakage on fluorescein angiography. B-scan ultrasonography and anterior segment ultrasound biomicroscopy of the right eye showed peripheral ciliochoroidal effusion. He had recently started intensive cervical traction therapy for the treatment of cervical spinal stenosis. There was spontaneous resolution of the choroidal effusion and intraretinal fluid after stopping cervical traction treatments. Optical coherence tomography imaging after resolution of the intraretinal fluid revealed thinning of the outer nuclear layer and attenuation of the ellipsoid and interdigitation zones corresponding to a persistent paracentral scotoma, consistent with acute macular neuroretinopathy. Conclusion: This is the first report of adverse ocular effects of cervical traction. We postulate that venous and arterial compromise during cervical traction therapy resulted in both ciliochoroidal effusion and a watershed infarct in the outer retina. Abstract : The authors present a case of ciliochoroidal effusion and presumed acute macular neuroretinopathy associated with cervical traction therapy for the treatment of cervical spinal stenosis.